Clinical experiences and case review of angiotensin II receptor blocker‐related angioedema in Korea. Issue 1 (20th August 2018) - Kim, Hyunah; Baik, Seo Yeon; Yang, So Jung; Kim, Tong Min; Lee, Seung‐Hwan; Cho, Jae Hyoung; Choi, In Young; Kim, Ju Han; Yoon, Kun‐Ho; Kim, Hun‐Sung
Abstract: Although angiotensin‐converting enzyme inhibitor‐related angioedema is well known, angiotensin II receptor blocker (ARB)‐related angioedema has not been extensively studied because of its lower incidence. Therefore, ARB‐related angioedema is likely to be overlooked in the clinical setting. We analysed the medical records of adults who had been prescribed ARB and diagnosed with angioedema between 2009 and 2015. All adults over the age of 18 years who were initially administered ARB between 1 January 2009 and 31 December 2015 were selected as participants in this study. To confirm whether the angioedema was actually due to the administration of ARB, we conducted a chart review. A total of 35 584 patients were prescribed ARB for the first time when visiting the Seoul St. Mary's Hospital during the study period. Twenty‐four patients diagnosed with angioedema for other reasons prior to their first prescription of ARB were excluded from this study. ARB‐related angioedema was suspected in six of 35 560 patients (0.02%) who were initially prescribed ARB during the study period. The manifestation of ARB‐related angioedema ranged from several days (1/6 case) to several years (3/6 cases). Some patients continued taking ARB with intermittent antihistamine or steroid therapy. In such cases, angioedema symptoms improved but did not completely resolve. Its diagnosis can be delayed and the symptoms may be recurrent as symptoms improve with antihistamine use. In some cases, the same person had different reactions depending on the type of ARB. Definitively diagnosing ARB‐related angioedema is difficult, and physicians often overlook angioedema without suspecting that it is an adverse effect of ARB. Close attention of physicians and improved patient education can reduce the incidence of ARB‐related angioedema.